- Efficacy of Tyrosine Kinase Inhibitors on serum biomarkers including thyroglobulin , thyroglobulin antibodies, and protein kinase B of Thyroid Cancer patients: Tyrosine Kinase Inhibitors on serum biomarkers - Miao, Bingliang (Journal of Medical Biochemistry, 2025)
Objective: it was to investigate the impact of the tyrosine kinase inhibitor Apatinib as an adjunct to 125I particle implantation therapy in thyroid cancer patients. Methods: data from 130 cases of thyroid cancer patients were collected. Based on treatment methods, 62 cases were categorized into the control group (CG, 125I particle implantation therapy alone) and 68 cases into the experimental group (EG, 125I particle implantation therapy + Apatinib). Clinical efficacy, thyroid function indices, ultrasound imaging features, serum biomarkers, and adverse events were compared between groups. Results: the objective response rate (82.26% vs. 73.33%) and disease control rate (91.94% vs. 80%) in EG were greatly superior to those in CG (P<0.05). Triiodothyronine and serum thyroxine were markedly lower, while thyroid-stimulating hormone levels were notably higher in EG versus CG (P<0.05). EG showed drastically reduced maximum lymph node diameter, lymph node number, and calcification points versus CG (P<0.05). Levels of thyroglobulin, thyroglobulin antibodies, and protein kinase B were substantially lower in EG than in CG (P<0.05). The incidence of adverse reactions was comparable between EG (12.9%) and CG (11.76%) (P>0.05). Conclusion: Apatinib as an adjunct to 125I particle implantation therapy effectively suppresses thyroid function, reduces thyroid hormone levels, and holds great promise not only in enhancing treatment efficacy and suppressing thyroid cancer activity but also in demonstrating higher safety levels.